(untitled) (Libellarium: journal for research in the field of information and related sciences, 2018)
Digital technology is an important constituent of day-to-day life of the Net Geners, a generation born and growing up in an entirely different media and communication context in comparison to any other generation before. Traditional marketing strategies of publishers need to be revised in order to encompass information habits and competences of the new generation. Don Tapscott conducted an extensive survey of everyday habits of this generation and identified eight norms used in its activities: freedom, customization, scrutiny, integrity, collaboration, entertainment, speed, and innovation. The Net Geners wish to have an active role in creating new products and in making decisions related to the value of products. They are prosumers on whom guerrilla marketing doesn´t exert a great influence, instead, they discuss a product with friends and new young influencers in online communities (n-fluence networks). Tapscott suggests applying the concept of a 2.0 (ABCDE) marketing based on the consumer behaviour of the new generation – anyplace, brand, communication, discovery, experience. This paper analyses websites of 14 Croatian children´s and youth publishers in view of the implementation of the 2.0 marketing principles and their orientation on that segment of population. The aim of the paper is to pinpoint the shortcomings in the design and functions of the publishers’ websites related to the communication with children and youth and their active involvement in the publishing business. The results of the survey could contribute to the identification of suitable communication strategies for the Net Geners. Before analysing Croatian websites, an analysis was conducted of five British publishers with a longstanding tradition, which suggests high quality of their business organisation. The data collected was used to identify the 2.0 marketing principles on Croatian publishers’ websites: social engagement, branding, additional content, customization, an interface adapted to new generations, online communities, and social networks. Croatian publishers’ websites stimulate communication with children and youth only insufficiently. The publishers did not recognize the importance of n-fluence networks, the creation of new online communities or connecting with the existing ones. There is a lack of stimulating an active inclusion of this population segment in the creation of publishing products and in establishing their value, as well as the lack of building a consumer’s experience. The publishers should therefore collaborate with experts on education of children, but should also focus on the members of the Net Geners, especially those who have an influence on cultural and entertainment habits of that generation.